Justin Martyr’s Logos: Its Import for Dialogical Theology - Kristiatmo, Thomas (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2021)
Written ages ago, insights from the Fathers of the Church have shed light upon the way of doing theology from generation to generation until today. Their contribution is long-lived and such is also true in the case of St. Justin Martyr. His pivotal idea of logos spermatikos, developed to cross and connect the then seemingly unbridgeable systems—Greek philosophy and Christianity—proves to be valuable to this day. A rereading of his thought can be fruitful for constructing a way of doing theology that is open to the world, for the key concept of this apologetic father invites one to do theology not from one’s small enclosed world, but from the perspective of a dialogue; hence the related metaphors are encounter, connectedness, and conversation. Contemporary theologians whose concern is to keep creating a more dialogical theology may benefit from Justin Martyr’s exploration of logos. His legacy helps theologians today obtain a new vision. In this way, reading the Church Fathers is not so much of a study on some irrelevant fossils as a leap towards an ever-better future of doing theology.